Climate change and food security of India: adaptation strategies in the irrigation sector - Aggarwal, Pramod K.; Palanisami K; Khanna M; Kakumanu KR (2012)
Creation of a large irrigation potential has been the cornerstone of India’s agricultural growth and past food security. It is estimated that the irrigation sector in the country will be affected considerably by climate change due to a projected increase in absolute rainfall, intensity of precipitation, glacial-melt and flood, as well as drought events. These changes are projected to modify the supply of both surface and groundwater in each region. Climate change is likely to increase the demand for groundwater to manage increasing intermittent periods of limited water availability. Simulation studies on Indian river basins have shown that the availability of water in some parts of the country may decrease while there may be an enhanced intensity of floods in other parts of the country. Several adaptation strategies are available for the irrigation sector. These include increasing the availability of usable water by conserving water resources, increasing the recharge and use of industrial and sewage wastewater. Other options are improving the efficiencies for water use, management of groundwater, water transfers between basins, trans-boundary cooperation and the increased use of modern tools in water resource management, such as remote sensing and GIS, and real time weather forecasts. It is concluded that demand management options will have a higher adaptation payoff than supply options.